Establishment of an Efficient Primary Culture System for Human Hair Follicle Stem Cells Using the Rho-Associated Protein Kinase Inhibitor Y-27632 - Wen, Lihong; Miao, Yong; Fan, Zhexiang; Zhang, Jiarui; Guo, Yixuan; Dai, Damao; Huang, Junfei; Liu, Zhen; Chen, Ruosi; Hu, Zhiqi (Frontiers in Cell and Developmental Biology, 2021)
Background: Hair follicle tissue engineering is a promising strategy for treating hair loss. Human hair follicle stem cells (hHFSCs), which play a key role in the hair cycle, have potential applications in regenerative medicine. However, previous studies did not achieve efficient hHFSC expansion in vitro using feeder cells. Therefore, there is a need to develop an efficient primary culture system for the expansion and maintenance of hHFSCs. Methods: The hHFSCs were obtained by two-step proteolytic digestion combined with microscopy. The cell culture dishes were coated with human fibronectin and inoculated with hHFSCs. The hHFSCs were harvested using a differential enrichment procedure. The effect of Rho-associated protein kinase (ROCK) inhibitor Y-27632, supplemented in keratinocyte serum-free medium (K-SFM), on adhesion, proliferation, and stemness of hHFSCs and the underlying molecular mechanisms were evaluated. Results: The hHFSCs cultured in K-SFM, supplemented with Y-27632, exhibited enhanced adhesion and proliferation. Additionally, Y-27632 treatment maintained the stemness of hHFSCs and promoted the ability of hHFSCs to regenerate hair follicles in vivo. However, Y-27632-induced proliferation and stemness in hHFSCs were conditional and reversible. Furthermore, Y-27632 maintained propagation and stemness of hHFSCs through the ERK/MAPK pathway. Conclusion: An efficient short-term culture system for primary hHFSCs was successfully established using human fibronectin and the ROCK inhibitor Y-27632, which promoted the proliferation, maintained the stemness of hHFSCs and promoted the ability to regenerate hair follicles in vivo. The xenofree culturing method used in this study provided a large number of high-quality seed cells, which have applications in hair follicle tissue engineering and stem cell therapy.